الأثر الديناميكي للنمو الاقتصادي على البطالة-دراسة حالة الجزائر- - Taleb, Soumia chahinez; Lebiq, Bachir (Finance and Business Economies Review, 2018)
This study aimed to analyze and measure the dynamic impact of economic growth on unemployment rates in the Algerian economy for the period (1985-2015) using the time series methods of the study variables. To achieve this goal, the dynamic relationship between unemployment rates and macroeconomic variables was estimated by using ARDL Bounds Testing Approach to Co-integration to estimate short- and long-term elasticities. The main findings of this study are: The components of the economic activity represented by both economic growth rates and capital accumulation rates have a slight impact on long-term unemployment rates. In the long term, unemployment rates don’t respond to both the volume of government expenditure and exports and imports, in addition, Phelps's relationship was not achieved. The study recommended that the structure of the Algerian economy should be reformed in such a way as to accommodate a larger number of workers and increase growth rates, while encouraging labor-intensive investments, thereby increasing real growth domestic product(GDP) and reducing unemployment